Efficiency of Geo Stationary Orbit (GSO) Natural Resources Utilization by Countries - Werner Wada Betu; Benny Djaja (Dinasti Research, 2024)
This article will discuss the efficient utilization of Geo Stationary Orbit (GSO). The research of this article aims to find out related to the utilization of GSO by countries that must be done efficiently so as to meet the needs of all mankind. The research method in this article is normative juridical. As a limited natural resource, GSO should be utilized jointly and efficiently so as not to exceed its orbital carrying capacity so as not to cause saturation. The utilization of GSO must be carried out rationally, efficiently and economically so that its access can be utilized equally for the benefit of all mankind by taking into account the needs of developing countries. GSO, which is part of space, is called the province of all mankind, so it cannot be claimed for ownership or sovereignty by the state. To achieve peace, the utilization of GSO must be done for the benefit of every country, regardless of its economic level or technological and scientific progress.